Evaluation of the micro-CATT, CATT/Trypanosoma brucei gambiense, and LATEX/T. b. gambiense methods for serodiagnosis and surveillance of human African trypanosomiasis in West and Central Africa - Truc Philippe; Lejon Veerle; Magnus Eddy; Jamonneau Vincent; Nangouma Auguste; Verloo Didier; Penchenier Laurent; Büscher Philippe (Bulletin of the World Health Organization, 2002)
OBJECTIVE: To evaluate the performance of serological tests using dried blood on filter-papers (micro-card agglutination test for trypanosomiasis (micro-CATT)) performed under field and laboratory conditions and using whole blood ((CATT/T.b. gambiense) (wb-CATT) and latex agglutination (LATEX/T.b. gambiense) (wb-LATEX)) for the serodiagnosis and surveillance of human African trypanosomiasis in West and Central Africa. METHODS: We evaluated the micro-CATT, wb-CATT and wb-LATEX methods in Côte d'Ivoire and the Central African Republic by screening 940 people. Sensitivity and specificity were calculated for each serological test; only patients with the confirmed presence of trypanosomes in the blood or lymph aspirate were considered true positives. Positive and negative predictive values were also calculated. FINDINGS: Each of the tests showed a lower sensitivity in the Central African Republic than in Côte d'Ivoire. CONCLUSION: The results confirmed the efficiency of the classic wb-CATT to detect sleeping sickness patients. The micro-CATT method can be used for human African trypanosomiasis surveillance if the test is performed on the same day as the blood collection, or if samples are stored at 4 ºC. Otherwise, micro-CATT can be used when absolute sensitivity is not required. wb-LATEX should only be used for high-specificity screening.